PENINGKATAN MINAT BELAJAR MATEMATIKA MELALUI PERMAINAN KARTU "JENDRAL PERKALIAN" BERBANTUAN TEKNIK JARI PADA SISWA KELAS V SD: Penelitian tindakan - Obaja Ratu Awae; Adi Winanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This classroom action research with a qualitative approach aims to improve interest in learning mathematics and multiplication skills for numbers 6-9 through the "Jendral Perkalian" card game assisted by finger techniques for fifth-grade students at SD Negeri 53 Manado. The research subjects consisted of 32 students (17 male, 15 female) selected through purposive sampling. The research was conducted in two cycles using the Kemmis and McTaggart model. Data were collected through participatory observation, interviews, field notes, learning interest questionnaires, and documentation. Data analysis used the Miles and Huberman model (data reduction, data presentation, and conclusion drawing). The results showed an increase in students' learning interest from the low category (45.60%) to the very high category (88.88%) in cycle II. The average multiplication score increased from 64 to 82.28, with classical completeness rising from 46% to 86%. Response time per question decreased from 12-15 seconds to an average of 4 seconds. Qualitative analysis showed increased student engagement and awareness that they were learning—not just playing. This research concludes that the "Jendral Perkalian" card game assisted by finger techniques is effective in increasing interest in learning and multiplication skills for elementary school students. These findings recommend the use of card game media as an alternative for fun and meaningful multiplication learning in elementary schools.